STEADY STATE ANALYSIS OF UNSATURATED FLOW ABOVE A SHALLOW WATER-TABLE AQUIFER DRAINED BY DITCHES - Kao C.; Bouarfa S.; Zimmer D. (My University, 2001)
The one-dimensional pressure head profile above a fixed water-table was studied for different steady infiltration rates. As shown in previous studies, when the infiltration rate (qin) is less than the soil saturated hydraulic conductivity (Ks), this profile can be divided into two parts: (1) from the water-table surface (z0) to an elevation zγ, the pressure head varies from 0 to a value hγ such as K(hγ)=-qin; (2) above the elevation zγ the pressure head is constant and equal to hγ. Above the water-table the zone where the pressure head is variable has been called 'transition zone'. Its height is shown to be highly variable and to depend on soil properties as well as on the infiltration rate. This transition zone is not the 'capillary fringe' as defined by Gillham (Gillham R.W., 1984. The capillary fringe and its effect on water-table response. J. Hydrol. 67, 307-324). Numerical experiments performed with HYDRUS-2D(R) for the case of a water-table drained by parallel ditches have shown that the height of the transition zone is similar in the one-dimensional profile and in the two-dimensional system as long as the local slope of the water-table is small. This result is important since in a two-dimensional system, the transition zone is the place where all the horizontal component of the unsaturated flow occurs. The ratio of the horizontal component of the unsaturated flow vs the total horizontal flow in both the unsaturated and saturated zones has been computed. For a given soil, this ratio decreases as the infiltration rate increases; for a given infiltration rate, the soil with the thinnest transition zone transfers the largest amount of water above the water-table.
Keywords: WATER-TABLE; UNSATURATED ZONE; CAPILLARY FRINGE; STEADY STATE; MODELING